Penerapan Variasi Teknik Anyaman Pada Busana Exotic - Edi Suwasana; Afidatun Nisa (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
Weaving is a unique variation whose manufacturing method is quite complicated and requires precision and patience. The process of making woven fabric which is quite complicated with unique results makes the writer interested in choosing woven as a variation of dramatic exotic clothing in the clothing. The problem discussed is how to apply variations of woven techniques to dramatic exotic clothing. The aim is to find out how to apply variations of woven techniques to dramatic exotic clothing. The benefit is to know about how to apply variations of woven techniques to dramatic exotic clothing. The method used is the method of research and development (research and development). The process of applying variations of weaving techniques in dramatic exotic clothing is as follows: making designs, determining the materials and weaving techniques to be used, preparing the tools and materials, taking measurements, making patterns, cutting fabrics, merging, pressing, weaving, making trials, sewing the clothing, applying weaving to clothing. The completion process is soom stitching and attaching the buttons. In the process of weaving, it is better to use a used cardboard base or Styrofoam, then both ends of the material are pinned using a pin to ease the weaving process. For woven braids, it should be decorated with stitches to beautify the appearance and maintain the shape of the weaving. The four-axis weaving should be pinned by hand sewing using a hand sewing needle and the thread to maintain the shape of the weaving.